Formation of zirconia foams using the thermostimulated sol-gel transition - Santos, E. P.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Elsevier B.V., 2002)
In this paper we describe the production of zirconia-based foams by a novel thermostimulated sol-gel route, that employs the foaming of colloidal suspensions prior to the sol-gel transition promoted by small increase of temperature (congruent to3 degreesC). This method produces gelled bodies having porosity >70% in the wet stage, and can be used to produce complex-shaped components. The effect of a foaming agent (Freon11 or CCl3F) and surfactant content on the formation and stability of the foams was analyzed. The rheologic measurements demonstrate that by increasing the surfactant concentration, the gelation time decreases increasing foam stability. As the surfactant concentration and quantity of foaming agent increase, the density decreases and the porosity increases. Hg porosimetry results show that the dry foam presents a bimodal pore size distribution. The family of sub-micrometer pores was attributed to the formation of a microemulsion between Freon11 and water. Scanning electron microscopy analysis shows that the foam structure consists of a three-dimensional network of spherical pores, which may be open and interconnected or closed, at larger or smaller porosities, respectively. Finally these results show that the thermostimulated sol-gel transition provides a potential route for ceramic foam manufacture. (C) 2002 Elsevier B.V. B.V. All rights reserved.